A Randomized Switch From Nevirapine-Based Antiretroviral Therapy to Single Tablet Rilpivirine/Emtricitabine/Tenofovir Disoproxil Fumarate in Virologically Suppressed Human Immunodeficiency Virus-1-Infected Rwandans. (1st July 2016) - Collins, Sean E.; Grant, Philip M.; Uwinkindi, Francois; Talbot, Annie; Seruyange, Eric; Slamowitz, Deborah; Mugeni, Adeline; Remera, Eric; Niyonsenga, Simon Pierre; Nyirimigabo, Josbert; Uwizihiwe, Jean Paul; Dongier, Pierre; et al.
Abstract : There is a need to improve antiretroviral options in Africa. This study shows switching from a neviripine-based treatment to co-formulated rilpivirine/emtricitabine/tenofovir disoproxil fumarate in virologically suppressed Rwandans is safe and non-inferior to continued nevirapine-based therapy at 24 weeks. Abstract: Background. Many human immunodeficiency virus (HIV)-infected patients remain on nevirapine-based antiretroviral therapy (ART) despite safety and efficacy concerns. Switching to a rilpivirine-based regimen is an alternative, but there is little experience with rilpivirine in sub-Saharan Africa where induction of rilpivirine metabolism by nevirapine, HIV subtype, and dietary differences could potentially impact efficacy. Methods. We conducted an open-label noninferiority study of virologically suppressed (HIV-1 ribonucleic acid [RNA] < 50 copies/mL) HIV-1-infected Rwandan adults taking nevirapine plus 2 nucleos(t)ide reverse-transcriptase inhibitors. One hundred fifty participants were randomized 2:1 to switch to coformulated rilpivirine-emtricitabine-tenofovir disoproxil fumarate (referenced as the Switch Arm) or continue current therapy. The primary efficacy endpoint was HIV-1 RNA < 200 copies/mL at week 24 assessed by the US Food and Drug Administration Snapshot algorithm with a noninferiority margin of 12%. Results. Between April and September 2014, 184 patients were screened, and 150 patients were enrolled; 99 patients switched to rilpivirine-emtricitabine-tenofovir, and 51 patients continued their nevirapine-based ART. The mean age was 42 years and 43% of participants were women. At week 24, virologic suppression (HIV-1 RNA level <200 copies/mL) was maintained in 93% and 92% in the Switch Arm versus the continuation arm, respectively. The Switch Arm was noninferior to continued nevirapine-based ART (efficacy difference 0.8%; 95% confidence interval, −7.5% to +12.0%). Both regimens were generally safe and well tolerated, although 2 deaths, neither attributed to study medications, occurred in participants in the Switch Arm. Conclusions. A switch from nevirapine-based ART to rilpivirine-emtricitabine-tenofovir disoproxil fumarate had similar virologic efficacy to continued nevirapine-based ART after 24 weeks with few adverse events.